(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Rainfall and Snowfall induced landslides are one of the most common and damaging natural hazards on Jammu and Kashmir region that not only degrade land in hilly areas but additionally causing deaths and destruction on natural slopes and cause tremendous losses. These slope failures usually influence by rain intensities which vary with time that is extremely common in Jammu Kashmir highway. The intensity and time duration of rainfall over a catchment area decide the property and magnitude of the landslide occurred by the rainfall. Deep slope failure mostly occurred by long duration rain over a catchment area, whereas shallow failure is related to very short-term rain with high intensity. The study shows that slope geometry and rainfall intensity are the major affecting parameter which generally cause landslide by the action of depletion of water through the soil pores which leads to the development of lubrication effects between soil particles and hence reduction in shear strength parameter of soil particles. It also indicates that permeability and density of the soil also playing an important role in slope failure mechanism.